Does Chronic Sleep Fragmentation Lead to Alzheimer's Disease in Young Wild-Type Mice? - Ba, Li; Huang, Lifang; He, Ziyu; Deng, Saiyue; Xie, Yi; Zhang, Min; Jacob, Cornelius; Antonecchia, Emanuele; Liu, Yuqing; Xiao, Wenchang; Xie, Qingguo; Huang, Zhili; et al. (Frontiers in Aging Neuroscience, 2021)
Chronic sleep insufficiency is becoming a common issue in the young population nowadays, mostly due to life habits and work stress. Studies in animal models of neurological diseases reported that it would accelerate neurodegeneration progression and exacerbate interstitial metabolic waste accumulation in brain. In this paper we study whether chronic sleep insufficiency leads to neurodegenerative diseases in young wildtype animals without genetic predisposition. To this aim, we modeled chronic sleep fragmentation (SF) in young wildtype mice. We detected pathological hyperphosphorylated-tau (Ser396/Tau5) and gliosis in SF hippocampus. 18F-FDG-PET further revealed a significant increase in brain glucose metabolism, especially in the hypothalamus, hippocampus and amygdala. Hippocampal RNAseq indicated that immunological and inflammatory pathways were significantly altered in 1.5-month SF mice. More interestingly, differential expression gene lists from stress mice models showed differential expression patterns between 1.5-month SF and control mice, while Alzheimer’s disease, normal aging and APOEε4 mutation mice models did not exhibit any significant pattern. In summary, 1.5-month sleep fragmentation could generate AD-like pathological changes including tauopathy and gliosis, mainly linked to stress, as the incremented glucose metabolisms observed with PET imaging suggested. Further investigation will show whether SF could eventually lead into chronic neurodegeneration if the stress condition is prolongated in time.